The effect of high Intensity interval training versus moderate intensity continuous training on arterial stiffness and 24 h blood pressure responses: A systematic review and meta-analysis. Issue 4 (April 2019) - Way, Kimberley L.; Sultana, Rachelle N.; Sabag, Angelo; Baker, Michael K.; Johnson, Nathan A.
Abstract: Objectives: Greater arterial stiffness and poor 24 h blood pressure (BP) are recognized as indicators of poor cardiovascular health. Evidence has shown that high intensity interval training (HIIT) may be a superior alternative to moderate intensity continuous training (MICT) for improving cardiovascular disease risk factors such as cardiorespiratory fitness and vascular function. However, there are limited data comparing the effect of HIIT to MICT on central arterial stiffness and/or 24 h BP response. The purpose of this study was to compare HIIT versus MICT on central arterial stiffness and 24 h BP outcomes by systematic review and meta-analysis. Design: A systematic review and meta-analysis was conducted. Methods: Eligible studies were exercise training interventions (≥4 weeks) that included both HIIT and MICT and reported central arterial stiffness, as measured by pulse wave velocity and augmentation index and/or 24 h BP outcome measures. Results: HIIT was found to be superior to MICT for reducing night-time diastolic BP (ES: −0.456, 95% CI: −0.826 to −0.086 mmHg; P = 0.016). A near-significant greater reduction in daytime systolic (ES: −0.349, 95% CI: −0.740 to 0.041 mmHg; p = 0.079) and diastolic BP was observed with HIIT compared to MICT (ES: −0.349, 95% CI: −0.717 to 0.020 mmHg; p = 0.063). No significant difference was found for other BP responses or arterial stiffness outcomes. Conclusions: HIIT leads to a superior reduction in night-time diastolic BP compared to MICT. Furthermore, a near-significant greater reduction in daytime BP was found with HIIT compared to MICT. No significant difference was observed for changes to central arterial stiffness between HIIT and MICT.